A rough estimate of the proportion of global emissions from agriculture due to smallholders - Vermeulen, Sonja J.; Wollenberg, Eva Karoline (2017)
Smallholders in developing countries produce, on a very rough estimate, 5% of total global greenhouse gas emissions. This figure includes emissions due to both agriculture and land use change for agriculture. Mitigation actions in smallholder agriculture now could support farm livelihoods and more sustainable agriculture in the long run, but should only be introduced where they have the potential to advance rather than constrain rural development outcomes.